Big Data: Definition, Architecture & Applications - Humam Khalid Yaseen; Ahmed Mahdi Obaid (JOIV : International Journal on Informatics Visualization, 2020)
Big data is a term for massive data sets having large, more varied and complex structure with the difficulties of storing, analyzing and visualizing for further processes or results. The process of research into massive amounts of data to reveal hidden patterns and secret correlations named as big data analytics. These useful informations for companies or organizations with the help of gaining richer and deeper insights and getting an advantage over the competition. For this reason, big data implementations need to be analyzed and executed as accurately as possible. In this paper; Firstly, we will discuss what big data and how it is defined according to different sources; Secondly, what are the characteristics of big data and where should it be used; Thirdly, the architecture of big data is discussed along with the different models of Big data; Fourthly, what are some potential applications of big data and how will it make the job easier for the persisting machines and users; Finally, we will discuss the future of Big data.